Penerapan Semiotik Batik Nitis Sebagai Produk Unggulan Desa Puloniti, Kecamatan Bangsal, Kabupaten Mojokerto - Lina Desriana Pratiwi; Rizki Agung Novariyanto (CV. Multi Kreasi Media, 2025)
This community service activity aims to provide an understanding of the symbolic meaning of the Nitis batik motif as a superior product and skill to the people of Puloniti village and to reveal its role in empowering local communities. This service activity uses educational methods to the community in the form of socialization and training to the Puloniti village community to understand the meaning of visual elements of batik such as tendrils, rice, and jasmine motifs as representations of leadership, welfare, and sincerity values using Charles Sanders Peirce's semiotics. The results achieved after this service activity are that the people of Puloniti village understand that Nitis batik not only has aesthetic and cultural value, but also contains the Javanese philosophy of Netes-Nitis-Natas which strengthens the social identity of the community. In addition, the people of Puloniti village are becoming skilled in batik activities, so that batik activities play an important role in increasing the skills and income of the community, especially women. Thus, Nitis batik is a cultural symbol as well as an instrument for economic empowerment and preservation of local values.